Why Learning Arabic? (Maqasid Approach in Formulating Arabic Learning Curriculum) - Ahmad Zaki Annafiri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to carry out a Maqasid approach to learning Arabic. This study uses a qualitative approach with a descriptive analysis method. Researchers use the book Al Maqasid for Beginners by Jaser 'Audah as a primary source and studies of books, articles, journals, and related scientific works as a secondary source. Researchers will discuss three main aspects of learning Arabic: ḍaruriyyat, ḥajiyyat, and tahsiniyyat aspects. The results of this study: 1) In the ḍaruriyyat aspect, the things that need to be considered are the meaning of the concepts of Al-Ilah, Ar-Rab, Ad-Din, Ar-Rasul, Al-Ibadah, and At-Taqwa, then proceed to the related understanding haḍarah, thaqafah, umran, and tamaddun as part of Islamic civilization, 2) in the ḥajiyyat aspect, two main points need to be considered, namely the sense of the moment and social media as a weapon. These two points result from ‘hajah’ or the need for students as objects of education in the context of current developments, 3) the tahsiniyyat aspect of the purpose of learning Arabic can be implemented in learning Arabic in the interest of getting benefits, both material and political benefits. By exploring and interpreting these three aspects of the maqasid perspective, students can understand their purpose for studying Arabic properly.تهدف هذه الدراسة إلى تنفيذ منهج مقاصد لتعلم اللغة العربية. تستخدم هذه الدراسة المنهج النوعي مع طريقة التحليل الوصفي. يستخدم الباحثون كتاب المقاصد للمبتدئين لجاسر عودة كمصدر أساسي ودراسات الكتب والمقالات والمجلات والأعمال العلمية ذات الصلة كمصدر ثانوي. سيناقش الباحثون ثلاثة جوانب رئيسية لتعلم اللغة العربية: جوانب الصرريات والحجيات والتحسينيات. ونتائج هذه الدراسة: 1) من ناحية السريات ، فإن الأمور التي يجب مراعاتها هي معنى مفاهيم الإله والرب والدين والرسول والعبادة والعبادة. التقوى ، ثم انتقل إلى الفهم ذي الصلة الحارة ، والثقافة ، والعمران ، والتمدن كجزء من الحضارة الإسلامية، 2) في الجانب الحجيات ، هناك نقطتان أساسيتان يجب أخذهما في الاعتبار ، وهما الشعور باللحظة ووسائل التواصل الاجتماعي كسلاح. هاتان النقطتان ناتجتان عن